A Comprehensive Reading of The Confusion of The Split Identity in Samuel Beckett's " Not I" - Dhain, Ahmed Yasir (International Journal of Psychosocial Rehabilitation, 2020)
This study is distinctively restricted to the study of the split identity in investigating the relationship between the character and its numerous identities as in Samuel Beckett's "Not I". It aims to find out a solution for its problematic complex of identity in various ways. This study hypothesizes that the mystification of the split identity becomes a reference to more than one identity. It also shows the character simply involves some kind of ambiguity. The character focuses on the movement that breaks the monotonous rigidity of the play. It is divided into four sections, each analyzing a topic. Finally, the study has reached some conclusions that verify the hypothesis of the study.